2020
DOI: 10.3389/fsurg.2020.584578
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tubeless Urinary Catheter Protocol Enhanced Recovery After Minimally Invasive Lung Surgery

Abstract: Objectives: Although previous studies have shown the feasibility of non-intubated techniques, it is unknown whether avoiding urinary catheters can enhance recovery. This study aimed to determine whether the tubeless urinary catheter protocol is feasible and beneficial for minimally invasive lung surgery. Methods: Patients were randomized to the control group, completely tubeless group, and partially tubeless group. A propensity score–matched (PSM) analysis was performed to ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The presence of urinary catheters limits the development of day surgery. A previous study showed that in the case of normal renal function, when the operation time is not long, it is not necessary to insert a urinary catheter ( 16 ). The presence of chest tubes for draining gas and liquid has become an obstacle to thoracic day surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of urinary catheters limits the development of day surgery. A previous study showed that in the case of normal renal function, when the operation time is not long, it is not necessary to insert a urinary catheter ( 16 ). The presence of chest tubes for draining gas and liquid has become an obstacle to thoracic day surgery.…”
Section: Discussionmentioning
confidence: 99%
“…SCIP 9, one of the adopted requirements, mandates the removal of urinary catheters within 48 hr after surgery to reduce the risk of CAUTI (Centers for Medicare & Medicaid Services, 2017). Enhanced recovery after surgery (ERAS) is also recommended by the guidelines in cardiac and pulmonary surgery (Engelman et al., 2019) and immediate removal of the urinary catheter after surgery has shown advantages in clinical practice (Van Backer et al., 2019; Meillat et al., 2021; Okrainec et al., 2017; Wang et al., 2020). In perioperative management of lung cancer removal surgery, the advantages may include the reduction in adverse urethra irritation, risk of urinary tract infections, use of antibiotics and enhancement of early postoperative movement, which may facilitate rapid postoperative recovery and shorten the length of hospital stay.. Injecting warm normal saline into the bladder before removing the catheter has been shown to be an effective method to urge patients to urinate spontaneously after extubation (Chao and Mansuria, 2019; Mills et al., 2020; Wormer et al., 2017).…”
Section: Introductionmentioning
confidence: 99%